Die Abwanderung spanischer Arbeitnehmer in die Bundesrepublik Deutschland. Umfang, Ursachen, Herkunfts- und Zielgebiete - Leib, Jürgen; Mertins, Günter (ERDKUNDE, 1980)
In the period 1960 to 1978 almost 809,000 Spaniards entered the Federal Republic, more than half of whom were persons seeking employment. Fifty three per cent of them came from Andalusia and Galicia. The relatively high proportion of Madrid (9 per cent) in this work migration is to be attributed to its position as the most important area of Spanish internal migration. After one or two inner-Spanish stages (provincial capital and/or economic or industrial concentration areas like Madrid, Barcelona, Valencia/Alicante, the Basque provinces) a large percentage of migrants from predominantly agriculturally structured provinces leaves for Western or Central Europe. After discussion of the most important, regionally differentiated causes of and motives for emigration the spatial distribution of Spanish employees in the Federal Republic is examined. For the period 1961 to 1976 the proportion of the regions of greatest concentration (Rhine-Ruhr, Rhine-Main, Rhine-Neckar, Hamburg, Hanover, Nuremberg) remain almost constant. Numerous labour exchange areas present moreover a concentration of fellow countrymen conditioned by practices and centres of recruitment.